The Value of Second-Opinion Consultation in Nongynecologic Cytopathology. Issue 5 (1st November 2021) - Bailey, Gabrielle E; Graham, Ashleigh; Kahler, Jessica; Williamson, Bonnie; Adams, Christina; Maleki, Zahra; Rodriguez, Erika F
Abstract: Objectives: The value of consultation in pathology has been well documented in surgical pathology, but there are few comprehensive studies of consultation cases in cytopathology. Here we report our experience with cytopathology consultation cases at a large academic center. Methods: A review of consultation cases at our institution was performed by searching our laboratory information system. The contributing institution's diagnosis was compared with that rendered by the reviewing cytopathologist to assess major and/or minor diagnostic discrepancies. Results: In total, 928 cases were reviewed with the following distribution: fine-needle aspiration (FNA, 79.4%), exfoliative nongynecologic cytology (18.3%), and cases with both FNA and nongynecologic cytology (2.3%). There were 379 (40.8%) true consults and 549 (59.2%) confirming consults. A total of 586 (63.1%) cases were in agreement with the outside pathologist, 78 (8.4%) cases had major discrepancies, and 264 (28.4%) cases had minor discrepancies. Major discrepancies were most common for pancreas (38.5%), lymph node (11.5%), and soft tissue sites (9.0%). Conclusions: Of the cases, 8.4% had major diagnostic discrepancies between the original diagnosis and the consultation diagnosis, which is consistent with reported values in surgical pathology consultation studies. The findings support the importance of second-opinion consultation in cytopathology to guide patient care.